Laminar convective heat transfer in a microchannel with internal longitudinal fins - Foong Jun Li, Andrew; Narayanaswamy, Ramesh; Chandratilleke, Tilak (Elsevier, 2009)
A numerical study was conducted to investigate the fluid flow and heat transfer characteristics of a square microchannel with four longitudinal internal fins. Three-dimensional numerical simulations were performed on the microchannel with variable fin height ratio in the presence of a hydrodynamically developed, thermally developing laminar flow. Constant heat flux boundary conditions were assumed on the external walls of the square microchannel. Results of the average local Nusselt number distribution along the channel length were obtained as a function of the fin height ratio. The analysis was carried out for different fin heights and flow parameters. Interesting observations that provide more physical insight on this passive enhancement technique, and the existence of an optimum fin height are brought out in the present study.